Leadership Strategies for Enhancing Lecturer Performance in Islamic Higher Education Institutions - Boyke Azwar; Amiruddin Siahaan; Rusydi Ananda (Fitrah: Journal of Islamic Education, 2026)
This study aims to analyze leadership management strategies in improving lecturer performance at Private Islamic Higher Education Institutions, focusing on STAI Al-Hikmah Tebing Tinggi and STIT Batubara. The study examines lecturer performance conditions, coordination patterns between institutional leaders and study program administrators, and leadership strategies in strengthening the implementation of the Tri Dharma of higher education. A qualitative multisite design was employed, with data collected through in-depth interviews, participant observation, and document analysis. Data were analyzed using an interactive approach involving data reduction, data display, verification, and conclusion drawing, while credibility was ensured through source and method triangulation. The findings reveal that lecturer performance improvement is achieved through collaborative academic leadership, effective coordination, continuous professional development, and systematic monitoring and evaluation. Leadership strategies include strengthening pedagogical competence, promoting research and publication productivity, enhancing community engagement, creating a supportive academic environment, and implementing sustainable reward mechanisms. The study concludes that collaborative and participatory leadership contributes significantly to strengthening lecturer professionalism, motivation, and academic productivity in Private Islamic Higher Education Institutions.